The Role of Omani Women in Achieving Sustainability in Light of Oman Vision 2040 - Al-abri, Laila Suwaid Said (The Arab Journal of Administration, 2025)
The study aimed to identify the role of Omani women in achieving sustainability (environmental, social, and economic dimensions) in light of Oman Vision 2040. The study sample included (191) women who hold leadership positions in Omani ministries, and the descriptive approach was used as a method for the study. The questionnaire was used as a tool for the study, and through applying the questionnaire many results were reached. The role of Omani women in achieving sustainability in light of Oman Vision 2040 came with a (medium) degree of response, in all dimensions (environmental dimension, social dimension, dimension The general average for the environmental dimension came with a degree of response (medium), with an arithmetic mean of (3.16) and a standard deviation of (.852). Likewise, the general average for the social dimension came with a degree of response (medium) and with an arithmetic mean of ability (3.23). And a standard deviation of (.764). The general average of the economic dimension also came in with a response rate of (medium), with an arithmetic mean of (3.21) and a standard deviation of (.844). The study recommended the necessity of organizing educational seminars for workers in all institutions about the importance of the leadership role. For women. Preparing a booklet that discusses the effectiveness of women’s leadership role and distributing it to workers in various institutions. The need to develop legislative and legal frameworks that provide for women’s right to hold leadership positions. The necessity of organizing training courses for women leaders on how to achieve sustainable development in all its social, environmental and economic dimensions.